High Diversity of Cytospora Associated With Canker and Dieback of Rosaceae in China, With 10 New Species Described - Pan, Meng; Zhu, Haiyan; Bonthond, Guido; Tian, Chengming; Fan, Xinlei (Frontiers in Plant Science, 2020)
Cytospora canker is a destructive disease of numerous hosts and causes serious economic losses with a worldwide distribution. Identification of Cytospora species is difficult due to insufficient phylogenetic understanding and overlapped morphological characteristics. In this study, we provide an assessment of 23 Cytospora spp. which covered nine genera of Rosaceae, and focus on 13 species associated with symptomatic branches or twigs canker and dieback disease in China. Through morphological observation and multilocus phylogeny of ITS, LSU, act, rpb2, tef1-α and tub2 gene regions, the results indicate 13 distinct lineages with high branch support. These include 10 new Cytospora species, i.e., C. cinnamomea, C. cotoneastricola, C. mali-spectabilis, C. ochracea, C. olivacea, C. pruni-mume, C. rosicola, C. sorbina, C. tibetensis, C. xinjiangensis and three known taxa include Cytospora erumpens, C. leucostoma and C. parasitica. This study provides an initial understanding of the taxonomy of Cytospora associated with canker and dieback disease of Rosaceae in China.